Penile Flap Inversion Vaginoplasty in Transgender Women: Contemporary Morbidity and Learning-Curve Analysis From a High-Volume Reconstructive Center - Maurer, Valentin; Howaldt, Marian; Feldmann, Inga; Ludwig, Tim; Vetterlein, Malte W.; Gild, Philipp; Weis, Sylvia; Marks, Phillip; Soave, Armin; Meyer, Christian P.; Fisch, Margit; Dahlem, Roland; et al. (Frontiers in Surgery, 2022)
Objectives Numbers of PIV are rising. The aim of this study is to analyze the surgical learning-curve (LC) on the grounds of perioperative complications. Patients and Methods 108 PIVs, performed by a single surgeon between 2015 and 2018 have been analyzed. Learning-curve analysis was based on three factors: operating time, vaginal depth and complications. Results The median FU was 6.3 months. Median age at surgery was 36 years, median time of hormone treatment was 36 months. The median CI was 0.3 and the median BMI was 25 kg/cm3. Median CCI® was 8.08. 40.7% of the patients developed short-term complications, more than half of which were Clavien I. Overall only 1.9% had Clavien IIIb complications. There were no Clavien IV or V complications. 17.6% of patients had wound infections, 13% wound dehiscence, 9.3% introitus strictures, 13.9% suffered from atrophy of the neovagina, i.e. loss of depth or width, and 8.3% from meatus urethrae strictures. Duration of hormonal therapy, BMI and CI had no impact on surgical outcome. Age had a significant impact on CCI®, as younger patients had a higher risk for complications. Use of scrotal skin and surgeries performed had a significant influence. LC analysis via CUSUM analysis showed that after 32 surgeries, the PIV is performed safely. Conclusion The PIV is a safe GAS-technique, associated with minor complications leading to low rates of revision surgery. Younger age, the use of scrotal skin and surgeon’s experience has significant impact on complications. Duration of hormonal therapy, circumcision and BMI has no impact on complications.